Analisis Peningkatan Produktivitas Kerja Pegawai Pada UMKM Sarung Batik Kalungguh Pekalongan - Ahmad Abdul Muiz; Efriyani Sumastuti; Rauly Sijabat (Jurnal Nuansa : Publikasi Ilmu Manajemen dan Ekonomi Syariah, 2023)
Expanding work productivity should be possible with different interesting methodologies and strategies by immediately addressing HR in the best way to build their proficiency and viability as an asset in the association. The results of the creation of Kalenggun batik sarong UMKM in Pekalongan in 2021 and 2022 are experiencing a downturn. This shows that there are still problems related to representative work efficiency so that they have not met organizational goals. This examination uses clear quantitative exploration techniques. Quantitative techniques, more specifically by testing existing speculations to trace the reality of these theories. Data collection methods used are literature and questionnaires. The results of this study indicate that leadership has a negative and not significant effect on the work productivity of the UMKM Batik Sarong in Pekalonga. Meanwhile, incentives, motivation, work environment and training have a positive and significant effect on the work productivity of the UMKM Sarung Batik Pekalongan.